(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
Vegetable artichoke of the mid-season variety Imperial Star in planting patterns of 70x30, 70x50, 70x70, 70x90 cm per hectare, respectively 47.6 - 28.5 - 20.4 - 25.8 thousand plants and plant growth, development, productivity and economic efficiency of technology growing. When planting seedlings in a field according to a 70x50 cm scheme, in the variant where 28.5 thousand plants were planted per hectare, the first fruits ripened 3-7 days earlier than with all planting schemes. From 544 g on one bush, 3.4-3.5 fruits (baskets) of 160 g each were formed. The yield (15.54 t/ha) is 29-85% higher compared to all options, the price of 1 kg of product is the cheapest ( 5189 soums), profitability indicator (285.4%) - 31st place compared to all options 226%